2021
DOI: 10.11591/ijece.v11i2.pp1510-1520
|View full text |Cite
|
Sign up to set email alerts
|

Real-time human detection for electricity conservation using pruned-SSD and arduino

Abstract: Electricity conservation techniques have gained more importance in recent years. Many smart techniques are invented to save electricity with the help of assisted devices like sensors. Though it saves electricity, it adds an additional sensor cost to the system. This work aims to develop a system that manages the electric power supply, only when it is actually needed i.e., the system enables the power supply when a human is present in the location and disables it otherwise. The system avoids any additional cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…The authors of [15] have revealed a method for combination error-dependent networks for picture classification. The authors of [16][25] attempted to use a mixed convolutional neural network to recognize macular abnormalities in SD-OCT images. [17].…”
mentioning
confidence: 99%
“…The authors of [15] have revealed a method for combination error-dependent networks for picture classification. The authors of [16][25] attempted to use a mixed convolutional neural network to recognize macular abnormalities in SD-OCT images. [17].…”
mentioning
confidence: 99%